Seroprevalence of Schmallenberg virus infection in sheep and goats flocks in Germany, 2012–2013. Issue 1 (11th January 2016) - Helmer, Carina; Eibach, Regina; Humann‐Ziehank, Esther; Tegtmeyer, Philip C.; Bürstel, Daniela; Mayer, Kathrin; Moog, Udo; Stauch, Sieglinde; Strobel, Heinz; Voigt, Katja; Sieber, Philipp; Greiner, Matthias; et al.
Abstract : Schmallenberg virus (SBV) is a member of the family Bunyaviridae and mainly affects ruminants. It is transmitted by biting midges, first and foremost Culicoides spp., and causes congenital malformations reflected in arthrogryposis–hydranencephaly (AH) syndrome. The aim of the study was to calculate the median within‐herd prevalence in small ruminant flocks in Germany in 2013. Therefore, 3800 serum samples were gained of 130 flocks in total. Summary: Schmallenberg virus (SBV) is a member of the family Bunyaviridae and mainly affects ruminants. It is transmitted by biting midges, first and foremost Culicoides spp., and causes congenital malformations reflected in arthrogryposis–hydranencephaly (AH) syndrome. The aim of this study was to collect data on the emergence of SBV as a new arthropod‐borne disease introduced into Europe in 2011. Germany was located in the core region of the 2011/2012 epidemic. Following two seroprevalence studies in the north‐west of Germany in 2012, this study focused on the epidemiology and distribution of SBV throughout 130 small ruminant flocks in the whole country. Blood samples were obtained of 30 animals per flock and a SBV‐specific questionnaire was used to collect operating data of the farms. The median within‐herd seroprevalence for all 130 flocks tested was 53.3% with a total range from 0% to 100%. The median within‐herd seroprevalence for goats was 30% [interquartile range (IQR): 40.3%] and 57% for sheep (IQR: 43.3%). Small ruminant flocks kept permanently indoors or housed overnight had a significantly lower seroprevalence than flocks kept permanently outdoors. In addition, this study revealed a significantly lower seroprevalence in the north‐east of Germany. These results show that small ruminants in Germany are still at risk of contracting new SBV infections following incomplete seroconversion of flocks especially in the north‐east of Germany. This might contribute to SBV becoming enzootic in central and northern Europe. Furthermore, the survey revealed that housing animals at least during mating and early pregnancy may reduce the risk of new SBV infections and may thus be an option to reduce losses as long as there is no licensed vaccine available on the German market.